Physicochemical, Sensorial and Calcium Bioavailability of Jelly Prepared Using Fish Gelatin in Combination with Furcellaran and Calcium L-Threonate - Petcharat, Tanyamon; Chaijan, Manat; Indriani, Sylvia; Karnjanapratum, Supatra; Nirmal, Nilesh; Singh, Jaspreet; Nairfana, Ihlana; Nalinanon, Sitthipong (My University, 2026)
Confectionery products, specifically jelly and gummy, require optimized structural, thermal, and nutritional properties for functionality and consumer acceptance. This study investigated the impact of furcellaran (FUR) and calcium L-threonate (Ca) on the physicochemical and the sensory properties of fish gelatin-based jelly (JFG). Furcellaran modestly enhanced gel strength and hardness, while its combination with calcium L-threonate produced synergistic improvements, with JFG-FUR-Ca achieving the highest gel strength (947.63 g) and hardness (78.14 N). Microstructural and intermolecular force analyses indicated that Ca2+ bridging between gelatin and furcellaran promoted ionic and hydrogen bonding, forming a dense and thermostable network. The combined incorporation of furcellaran and calcium L-threonate enhanced the rheological properties while preserving low syneresis. Sensory evaluation revealed minor reductions; however, overall acceptability was higher than 7. Calcium bioavailability after digestion through the gastrointestinal tract model remained high (70–80%), confirming effective calcium fortification. The synergistic incorporation of furcellaran and calcium L-threonate effectively improved the structural integrity, thermal stability, and calcium bioavailability of fish gelatin-based jelly, while maintaining acceptable sensory qualities, highlighting its potential as a functional calcium-fortified confectionery product.
Keywords: calcium fortification; calcium-fortified jelly; fish gelatin; furcellaran; gelling property